Diacylglycerol Kinase η Activity in Cells Using Protein Myristoylation and Cellular Phosphatidic Acid Sensor. Issue 4 (24th February 2021) - Ishizaki, Ayuka; Murakami, Chiaki; Yamada, Haruka; Sakane, Fumio
Abstract: Diacylglycerol kinase (DGK) phosphorylates diacylglycerol to produce phosphatidic acid (PtdOH) and regulates the balance between two lipid second messengers: diacylglycerol and PtdOH. Several lines of evidence suggest that the η isozyme of DGK is involved in the pathogenesis of bipolar disorder. However, the detailed molecular mechanisms regulating the pathophysiological functions remain unclear. One reason is that it is difficult to detect the cellular activity of DGKη. To overcome this difficulty, we utilized protein myristoylation and a cellular PtdOH sensor, the N‐terminal region of α‐synuclein (α‐Syn‐N). Although DGKη expressed in COS‐7 cells was broadly distributed in the cytoplasm, myristoylated (Myr)‐AcGFP‐DGKη and Myr‐AcGFP‐DGKη‐KD (inactive (kinase‐dead) mutant) were substantially localized in the plasma membrane. Moreover, DsRed monomer‐α‐Syn‐N significantly colocalized with Myr‐AcGFP‐DGKη but not Myr‐AcGFP‐DGKη‐KD at the plasma membrane. When COS‐7 cells were osmotically shocked, all DGKη constructs were exclusively translocated to osmotic shock‐responsive granules (OSRG). DsRed monomer‐α‐Syn‐N markedly colocalized with only Myr‐AcGFP‐DGKη at OSRG and exhibited a higher signal/background ratio (3.4) than Myr‐AcGFP‐DGKη at the plasma membrane in unstimulated COS‐7 cells (2.5), indicating that α‐Syn‐N more effectively detects Myr‐AcGFP‐DGKη activity in OSRG. Therefore, these results demonstrated that the combination of myristoylation and the PtdOH sensor effectively detects DGKη activity in cells and that this method is convenient to examine the molecular functions of DGKη. Moreover, this method will be useful for the development of drugs targeting DGKη. Furthermore, the combination of myristoylation (intensive accumulation in membranes) and α‐Syn‐N can be applicable to assays for various cytosolic PtdOH‐generating enzymes.